2018
DOI: 10.1097/ijg.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of XEN Gel Implant in Eyes With Pseudoexfoliative Glaucoma

Abstract: The XEN gel implant as a standalone or combined procedure demonstrated similar efficacy and safety results in PEXG and POAG eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 16 publications
5
34
0
4
Order By: Relevance
“…In two of the XEN ® 45-implantation procedures a dry-lake bleb reconversion [13] was performed, while none of the XEN ® 63 procedures required one. If we compare our outcomes with those published in the literature, in De Gregorio's [16] study, 2.4% of the patients required needling, while in Mansouri et al [15] as much as 36% of the open-angle glaucoma patients had to undergo needling. Such a low rate could be due in our case not only to the surgeon's experience as well as to the consistent application of subconjunctival mitomycin prior to the procedure.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In two of the XEN ® 45-implantation procedures a dry-lake bleb reconversion [13] was performed, while none of the XEN ® 63 procedures required one. If we compare our outcomes with those published in the literature, in De Gregorio's [16] study, 2.4% of the patients required needling, while in Mansouri et al [15] as much as 36% of the open-angle glaucoma patients had to undergo needling. Such a low rate could be due in our case not only to the surgeon's experience as well as to the consistent application of subconjunctival mitomycin prior to the procedure.…”
Section: Discussionmentioning
confidence: 82%
“…Mansouri et al [15] also found a significant decrease of IOP although his study focused only on the first year of postimplantation follow-up, as did De Gregorio's et al [16], who reported in their study a 44% IOP drop. Moreover, it is worth pointing out that these two studies only assessed the XEN ® 45 Gel Stent and that Mansouri's included not only patients with POAG but also pseudoexfoliative glaucoma cases.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Consistent with the American Academy of Ophthalmology's Preferred Practice Pattern Guidelines [1], needling was part of the standard postoperative care to improve aqueous flow and lower IOP based on the investigator's clinical assessment of bleb function. Consistent with other recent studies [18,19], needling was not considered an adverse event (AE) or glaucomarelated secondary surgical intervention (SSI) but was documented as a postoperative procedure; it could be performed at any point in the postoperative period, as believed necessary by the investigator. No specific protocol was mandated, and use of an antifibrotic agent at the time of needling was also left to the investigator's discretion.…”
Section: Perioperative Proceduresmentioning
confidence: 86%
“…Mansouri et al compared 57 eyes with POAG and 53 eyes with PXG and demonstrated equal efficacy and safety for both treatment groups. [21] The PXG eyes were noted to have a 31% IOP drop at 12 months and a 63% success rate as compared to 30% and 42%, respectively, for POAG eyes. In a study on 24 uveitic eyes, Sng et al noted a 60% IOP decline at post-operative month 12 with 83% eyes requiring no further glaucoma surgery.…”
Section: Intraocular Pressure Controlmentioning
confidence: 91%